Prototype Perkakas Mekanik Berbasis Benda Kerja Praktik Mahasiswa - Abdul Tahir; Edi Rande Padang; Harjuma Harjuma; Fitriana Firdaus (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The learning process for vocational higher education applies a composition of 30 percent theory and 70 percent practice. A larger composition of practical learning will guarantee an increase in the quality of students' expertise, because in practical learning students practice in workshops that produce workpieces in the form of products that have economic value. Workpieces are made by manufacturing processes using industrial-based machines such as lathes, milling machines, drills, grinders, and others. Practical work in the workshop is carried out for one week or the equivalent of 38 hours. The quality of the workpiece is also a parameter for student assessment which will become one of the semester graduation requirements so as to produce quality students in their fields. However, there are problems in practicum activities in the vocational field that are most experienced by almost all vocational education institutions, namely workpiece waste. Vaccination education managers must think about how to optimize or utilize work objects resulting from student practice. Not a few students' work is ignored or thrown away and not utilized. This is the background of this research. This study aims to make mechanical device products that have economic value by utilizing students' work. The product manufacturing method begins with data collection, planning and drawing, the manufacturing process, assembling, and testing. From the results of the tool making, 4 types of prototype products were obtained, namely table vise, bending tools, C clamps, mini press tools. From the four products made, it can be concluded that the tool manufacturing process went according to plan and optimal results were obtained.